TINGKAT PARTISIPASI POLITIK MASYARAKAT DALAM PILKADES SERENTAK TAHUN 2019 - Riza Umami; Catur Wido Haruni; Fitria Esfandiari (Indonesia Law Reform Journal, 2021)
One of the means to channel democracy is through the Village Head Election. Democracy inthe context of village head elections can be understood as an acknowledgment of the diversityand attitudes of community political participation from the community within a democraticframe at the village level. Participation is essential to research, considering an election'ssuccess can be seen from the level of community participation. The formulation of this study'sproblems is 1) What is community political participation in the simultaneous village headelection in East Java. 2) What factors increase the level of community political participation inthe Pilkades Simultaneously in East Java. In this study the authors used an empirical juridicalresearch approach from primary and secondary data sources with data collection usinginterviews, observation and documentation and data analysis used was descriptive qualitative.This study concludes that the level of public political participation in the PilkadesSimultaneously in East Java from 2013 to 2019 increases annually. This is evidenced by voters'level in each village having a high percentage, namely, village A increased by 32%, Village B2%, Village C 16%, and Village D 16%. This happens because several factors, such as: first,internal's factors, include socioeconomic, age, and awareness of political society.Simultaneously, external’s factors have political aspects of money, environment, information, and the figures from the village head candidate itself. The community must continue to raiseawareness of the importance of political participation. The government must also intensifyuseful programs to stimulate the community's attractiveness to play a more active role in thevillage's betterment.